2015
DOI: 10.1186/s40478-015-0261-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of glucose-metabolizing enzymes in multiple sclerosis lesions

Abstract: IntroductionDemyelinated axons in multiple sclerosis (MS) lesions have an increased energy demand in order to maintain conduction. However, oxidative stress-induced mitochondrial dysfunction likely alters glucose metabolism and consequently impairs neuronal function in MS. Imaging and pathological studies indicate that glucose metabolism is altered in MS, although the underlying mechanisms and its role in neurodegeneration remain elusive. We investigated expression patterns of key enzymes involved in glycolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…More complex is the scenario in MS, where cellular metabolism varies according to the activity of the disease. Specifically, in active MS demyelinating lesions, characterized by the presence of activated microglia and macrophages, increased levels of PDH complex, malate dehydrogenase (MDH) and KGDH were detected compared to normal white matter, indicating that glycolytic and TCA cycle pathways were increased [86]. On the contrary, in demyelinated axons, namely, inside the inactive lesion (plaque), KGDH activity was reduced, thus correlating with terminal axonal damage [86].…”
Section: Role Of Mitochondria and Neuroinflammation In Neurodegeneratmentioning
confidence: 99%
See 1 more Smart Citation
“…More complex is the scenario in MS, where cellular metabolism varies according to the activity of the disease. Specifically, in active MS demyelinating lesions, characterized by the presence of activated microglia and macrophages, increased levels of PDH complex, malate dehydrogenase (MDH) and KGDH were detected compared to normal white matter, indicating that glycolytic and TCA cycle pathways were increased [86]. On the contrary, in demyelinated axons, namely, inside the inactive lesion (plaque), KGDH activity was reduced, thus correlating with terminal axonal damage [86].…”
Section: Role Of Mitochondria and Neuroinflammation In Neurodegeneratmentioning
confidence: 99%
“…Specifically, in active MS demyelinating lesions, characterized by the presence of activated microglia and macrophages, increased levels of PDH complex, malate dehydrogenase (MDH) and KGDH were detected compared to normal white matter, indicating that glycolytic and TCA cycle pathways were increased [86]. On the contrary, in demyelinated axons, namely, inside the inactive lesion (plaque), KGDH activity was reduced, thus correlating with terminal axonal damage [86]. These findings suggest that the TCA cycle is definitely altered in NDDs, but upregulation or downregulation of its enzymes might change according to the type of disease and the type of cells involved.…”
Section: Role Of Mitochondria and Neuroinflammation In Neurodegeneratmentioning
confidence: 99%
“…In MS, the focus has been mainly on metabolic disturbances within the CNS, especially in neurons and axons, and mitochondrial injury as well as changes in glucose-metabolizing enzymes have been described in active MS lesions (57)(58)(59). In peripheral immune cells from RRMS patients, a pilot study suggested that immune cells from RRMS patients might exhibit altered activities in several complexes of the electron transport chain as well as key enzymes of glycolysis such as hexokinase I pointing towards an impaired mitochondrial respiration and concomitantly decreased glycolytic activity; however, the patient cohort investigated was rather small and active and stable patients were not separately investigated (16,60).…”
Section: Comparison Of Metabolic Profiles Of Activated High-affinity mentioning
confidence: 99%
“…The alteration of energy metabolism also is found in serum of MS patients (Tavazzi et al, ). Moreover, glycolytic shift may contribute to ongoing axonal degeneration in MS (Nijland et al, ).…”
Section: The Role Of Warburg Effect In Brain Diseasesmentioning
confidence: 99%